2021
DOI: 10.3390/life11060543
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Large Osteochondral Lesions in the Knee: Focus on Fixation Techniques

Abstract: Large (>3 cm2), focal osteochondral lesions (OCL) may result in poor functional outcomes and early secondary osteoarthritis of the knee. The surgical management of these OCL remains challenging. The treatment strategy must be tailored to various aspects, including lesion-specific (e.g., size, location, chronicity), joint-specific (e.g., instability, limb alignment, meniscal status), and patient-specific factors (e.g., age, activity level, comorbidities). Simple chondroplasty and bone marrow stimulation (BMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The stability of the patellofemoral joint is extremely crucial to prevent early knee osteoarthritis. Niemeyer et al suggested that any osteochondral flake fracture indicates surgical treatment with the objective of internal fixation in both pediatric and adult patients [ 9 ]. Alosaimi et al and Bhatt et al also reported a similar case report of osteochondral fracture of the patella not associated with patellar dislocation in the adolescent age group [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of the patellofemoral joint is extremely crucial to prevent early knee osteoarthritis. Niemeyer et al suggested that any osteochondral flake fracture indicates surgical treatment with the objective of internal fixation in both pediatric and adult patients [ 9 ]. Alosaimi et al and Bhatt et al also reported a similar case report of osteochondral fracture of the patella not associated with patellar dislocation in the adolescent age group [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our patient had a very large osteochondral fracture fragment involving almost the whole of the medial patellar facet. Hence, due to the improved understanding of patellofemoral pathologies, a variety of arthroscopic and open-surgical concepts for the repair of osteochondral lesions and the restoration of joint stability have been developed [ 9 ]. Multiple treatment options are available for managing osteochondral fractures, including fixation of the displaced fragment, use of the regenerative procedure, or removing the osteochondral fragment [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important benefit of the refixation is that it can be performed as a one-step procedure in contrast to the 2-step procedure of ACI. In addition, the refixation of the fragment allows preserving the original hyaline cartilage while ACI can form hyaline-like cartilage only [34]. Nevertheless, ACI is an excellent fallback option with similar good clinical and radiological outcome and should always be discussed with the patient before the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When refixation is not possible along with fragment removal, other techniques such as microfracture of the subchondral bone (MF) and autologous chondrocyte implantation (ACI) can also be used [ 18 , 19 ]. The microfracture of the subchondral bone is made in order to harvest bone marrow mesenchymal stem cells to reconstruct the cartilage defect.…”
Section: General Presentation Of the Knee Osteochondral Fracturesmentioning
confidence: 99%